Three Lions on Her Shirt: Hot and Banal Nationalism for England's Sportswomen. (December 2019) - Bowes, Ali; Bairner, Alan
It has long been claimed that sport plays an important role in the formulation of national identity. Key to understanding this relationship is Michael Billig's concept of banal nationalism, which is used in this article to examine national symbols that act as daily reminders of the nation. Specifically, the article discusses the relationship between Englishness and sport by drawing upon data from interviews with representative English sportswomen in association football, cricket, netball, and rugby union. The article demonstrates the important role that (men's) sport plays in developing a sense of national identity in England and, in particular, one that is distinct from Britishness. Furthermore, the significance of national symbols is evidenced as banal reminders of national identity for England's sportswomen.